Effect of Electron Radiations on the Physical Properties of Laminated Particle Boards - Hesami, Majid; Gupta, Arun; Jaafar, Abdullah; Avazpour, Mahrokh (Asian Online Journals, 2015)
In the present work, the particleboards laminated with melamine formaldehyde and Polymer Faced Chipboard(PFC) paper were radiated with different dosages of electron radiations and its impact on the polymerization and other chemical properties were analyzed using characterization techniques such as TGA, DSC and XRD. It was observed that the amount of radiations have effect on the physical and thermal properties of the lamination. The knowledge from the present work will be used to develop new kind of coatings using melamine formaldehyde and PFC polymer and later on radiate it with the electron radiations to improve its thermal and mechanical properties.